Carbonation of steelmaking slag presents an opportunity for carbon neutral: A review. Issue 54 (December 2021) - Chen, Zhaohou; Cang, Zhizhi; Yang, Fengmin; Zhang, Jingwen; Zhang, Lingling
Highlights: Carbonation of Steelmaking slag can reduce almost 12–17 % of CO2 emissions from iron and steel industry. BOF slag exhibits relatively superior performance in CO2 sequestration and conversion. Direct aqueous carbonation is more effective way than the other ways. Abstract: An ambitious goal has been set to limit global temperature increase within 1.5℃ above pre-industrial levels. Iron and steel industry as one of the main industrial sectors, has always been accompanied by high energy input and high carbon dioxide emissions. Carbon capture and storage is one of the important technologies for the iron and steel industry to achieve deep reduction of emissions. Economic and effective material for carbon dioxide sequestration is still a problem that needs to be solved. In order to meet the challenges of the future, the feasibility of using steelmaking slag to promote carbon neutral in the iron and steel industry is discussed in this study. The present work systematically reviews the carbonation of steelmaking slag from three aspects: the carbonation processes and mechanism of steelmaking slag; the effect of operational conditions on carbon dioxide sequestration ratio and reaction rate; and carbon dioxide sequestration capacity of different types of steelmaking slag. The results show that steelmaking slag has a great potential for carbon dioxide sequestration, which can reduce almost 12–17 % of carbon dioxide emissions from the iron and steel industry. Moreover, challenges faced by the use of steelmaking slag for carbon dioxide sequestration and the prospects for the utilization of carbonated steelmaking slag are summarized.